Pak4 Induces Premature Senescence via a Pathway Requiring p16(INK4)/p19(ARF) and Mitogen-Activated Protein Kinase Signaling - Cammarano, Marta S. (American Society for Microbiology, 2005)
Exposure of primary cells to mitogenic stimuli or oncogenes often causes them to undergo premature senescence. This is most likely a protective function that prevents uncontrolled proliferation. Pak4 is a target for the Rho GTPase Cdc42. Pak4 is overexpressed in human tumor cell lines, and it is the only member of the Pak family that is highly transforming in immortalized fibroblasts. Here we show that in primary fibroblasts, activated Pak4 inhibits cell proliferation and promotes premature senescence. Furthermore, Pak4 expression levels are upregulated in response to stimuli that promote senescence. Pak4-induced arrest appears to be mediated by a pathway that requires the ERK mitogen-activated protein kinase, as well as the cell cycle inhibitors p16(INK4) and p19(ARF). These new results describing a role for Pak4 in senescence are important for understanding why this protein is associated with cancer and how it promotes transformation in immortalized cells.